Desain dan Implementasi Stopwatch Digital pada Kegiatan Praktikum Over-Current Relay - Jeremias Leda; Simon Patabang; Trials Jusuf; Dionisius Ardeni (Gapenas Publisher, 2022)
The use of a digital stopwatch as a timer for the overcurrent relay is important in order to know the operating time characteristics of the overcurrent relay. This activity aims to design and build a digital stopwatch prototype for laboratory practice activities. The design of the equipment circuit was then made a digital stopwatch prototype and applied to the practical implementation of the MCGG52 type overcurrent relay for laboratory activity in the electrical engineering laboratory at the Faculty of Engineering, Atma Jaya University Makassar. The practical activity to record the operating time of the MCGG52 overcurrent relay using a digital stopwatch was successfully carried out with results that met the working standards of the MCGG52 relay